FOXL2 in Human Endometrium: Hyperexpressed in Endometriosis. (October 2014) - Governini, Laura; Carrarelli, Patrizia; Rocha, Ana Luiza Lunardi; Leo, Vincenzo De; Luddi, Alice; Arcuri, Felice; Piomboni, Paola; Chapron, Charles; Bilezikjian, Louise M.; Petraglia, Felice
The present study investigated expression and protein localization of FOXL2 messenger RNA (mRNA) in endometrium of healthy women and in patients with endometriosis during endometrial cycle. In endometriotic lesions, FOXL2 mRNA and protein were evaluated and a possible correlation with activin A mRNA expression changes was also studied. Endometrium was collected from healthy women (n = 52) and from women with endometriosis (n = 31) by hysteroscopy; endometriotic tissues were collected by laparoscopy (n = 38). FOXL2 gene expression analysis in endometrium of healthy women showed a significant expression and no significant changes in mRNA levels between proliferative and secretory phases; a similar pattern was observed in endometrium of patients with endometriosis. Immunohistochemical evaluation showed that FOXL2 protein localized in stromal and glandular cells and colocalized with SUMO-1 . FOXL2 mRNA expression was 3-fold higher in endometriosis than in healthy endometrium ( P < .01) and a positive correlation between FOXL2 and activin A mRNA was found ( P < .05) in endometriosis. In conclusion, FOXL2 mRNA expression and its protein localization do not change during endometrial cycle in eutopic endometrium from healthy individuals or patients with endometriosis; the hyperexpression of FOXL2 in endometriotic lesions suggests an involvement of this transcriptional regulator, probably associated with activin A expression and related to the pathogenesis of endometriosis.